2020
DOI: 10.1002/admi.201902054
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing Low‐Temperature Atomic Layer Deposited TiO2 Electron Transport Layers with Metal Electrodes

Abstract: elevated temperatures and UV light. To improve the stability of perovskite solar cells and LEDs, researchers have pursued numerous approaches including depositing hydrophobic coatings on top of perovskites absorbers, [23][24][25][26] device encapsulation [21,[27][28][29] and tuning the composition of perovskites. [30][31][32][33][34] Atomic layer deposited (ALD) metal oxides such as ZnO, Al 2 O 3 , and TiO 2 have been shown to be quite effective as a protection layer for perovskite optoelectronic devices. [35,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Another metal oxide that has been adopted as a potential ETL is TiO 2 , although always in combination with a PCBM or C60 interlayer. 7,20,[32][33][34][35] The ALD process involved the application of tetrakis(dimethylamino)titanium(IV) (TDMA-Ti) and H 2 O, as the metalorganic precursor and coreactant, respectively. Despite these promising results in combination with organic interlayers, to the best of our knowledge, TiO 2 grown directly on top of the absorber has not been used as sole ETL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another metal oxide that has been adopted as a potential ETL is TiO 2 , although always in combination with a PCBM or C60 interlayer. 7,20,[32][33][34][35] The ALD process involved the application of tetrakis(dimethylamino)titanium(IV) (TDMA-Ti) and H 2 O, as the metalorganic precursor and coreactant, respectively. Despite these promising results in combination with organic interlayers, to the best of our knowledge, TiO 2 grown directly on top of the absorber has not been used as sole ETL.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the perovskite/TiO 2 interface has been so far a limited subject of investigation. 33,35,36 Among all ETLs grown directly on perovskites, SnO 2 is the most investigated. Palmstrom et al 10 adopted tetrakis(dimethylamino)tin(IV) (TDMA-Sn) as the metal precursor for SnO 2 and identified that effusion of the FA cation from the Cs 0.17 FA 0.83 Pb (Br 0.17 I 0.83 ) 3 perovskite occurs at temperatures of 100°C and above during the ALD process.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic layer deposited titanium dioxide (ALD-TiO 2 ) is a widely studied transition metal oxide thin film material, in part because of its chemical stability and its technologically important optical and electronic properties. Titanium oxide is a photocatalyst that activates photoinduced decomposition of organic contaminants so that TiO 2 coatings can produce “self-cleaning” surfaces. Furthermore, TiO 2 thin films also function as electron-selective contacts for optoelectronic devices including solar cells. Atomic layer deposited TiO 2 also serves as a barrier to oxidative corrosion of underlying efficient semiconductor light absorbers in aqueous electrolytes, , enabling stable water splitting for solar fuel synthesis. These varied and significant applications of thin TiO 2 films provide motivation for understanding the relationships among ALD synthesis conditions and the physical and chemical properties of atomic layer deposited TiO 2 .…”
mentioning
confidence: 99%
“…Because of this mechanism, the amount of additive deposited onto the H 2 -storage material can be controlled with great precision. ALD has successfully been used to protect and enhance the performance of nanostructured and highly porous materials at low temperatures as well as emerging and complex materials. Hence, we ultimately expect that (1) the ALD coating will encapsulate and maintain the nanostructure of Mg­(BH 4 ) 2 and (2) the catalyst (chemical additive) deposited can alter the Mg­(BH 4 ) 2 decomposition pathway that will enhance kinetics and H 2 reversibility.…”
Section: Introductionmentioning
confidence: 99%